Hubungan Kuat Tekan, Tarik Belah, dan Tarik Lentur Beton dengan Bahan Tambah akibat Penggunaan Metode Perencanaan Campuran yang Berbeda - Abdullah, Nora; Ranian, Cut; Hardi, Ivan; Kurniawan, Kurniawan; Syauki, Mukhayar (JURNAL TEKNIK SIPIL, 2022)
Due to the difference in concrete mix design method that applied in Standar Nasional Indonesia, SNI (Indonesian National Standard) in the last 25 years, which SNI 03-2834-2000 is adopted from DOE method and SNI 7656-2021 is adopted from ACI 211.1 methods, it is important to understand what is the relationship between concrete compressive strength with its tensile strength (splitting and flexural tensile strength) especially if there is an admixture applied in the concrete mixture. To study this relationship, specimens for each water cement ratio (0,35; 0,40; and 0,45) and super plasticizer dosage (0; 0,4 liter/100 kg PC; and 0,6 liter/100 kg PC) were prepared for compressive strength, splitting, and flexural tensile strength tests at 28 days. The main factor that affected concrete strength both for ACI 211.1 or DOE concrete mix design method is the aggregate composition. The results showed that the splitting tensile strength and the flexural tensile strength of concrete in this research is 4%-15% and 6%-21% of compressive strength, respectively. The decreasing trend of concrete compressive strength as the increasing of the water cement ration complied the general rule. While the increasing of super plasticizer dosage shows inclination trend of the compressive strength. However, the splitting and failure tensile strength shows different trend for interaction of concrete mixed design with super plasticizer dosage or with water cement ratio. In addition, the compressive strength to splitting tensile strength or flexural strength relationship in this research shows the similar trend with the ACI 318 and CEB-FIP codes but the compressive strength is less compare to both codes.